Integrated Optimization of Heterogeneous Fleet Deployment, Sailing Speed, and Bunkering Strategy Considering Adaptive Safety Stock - Muhammad Syolahudin Abdurrahman; Tresnaningati Sekar Pramesta; Lailatul Rohmah; Suprayogi Suprayogi; Andi Cakravastia; Rully Tri Cahyono (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2026)
Logistics cost inefficiencies often stem from fragmented operational policies. Volatile global fuel prices and unpredictable maritime schedules further complicate matters. Traditional isolated optimization methods frequently fail to ensure supply chain resilience. This study addresses these limitations by developing a Mixed-Integer Linear Programming (MILP) model. The model simultaneously integrates three core strategic decisions: heterogeneous fleet deployment, sailing speed optimization, and bunkering strategy. Inventory thresholds are dynamically adjusted based on real-time sailing conditions and port-to-port consumption rates, moving beyond static buffer assumptions. This model incorporates an adaptive stock mechanism to mitigate energy supply uncertainties at transit ports while minimizing total costs, which diverges from conventional approaches. The mathematical formulation is designed to minimize total operating expenses while accounting for technical constraints, such as fixed time windows and fluctuating cargo capacities. Optimization results show that integrating these variables effectively reduces cost inefficiencies. Quantitatively, the Proposed Scenario reduced Total Cost by 18.89%, saving USD 191,555 per service cycle compared to the Existing Scenario. The integrated approach uncovers a significant trade-off between speed reduction and inventory holding costs, identifying a more balanced operational equilibrium than previous models. The findings demonstrate that applying adaptive safety stock enhances the robustness of the bunkering strategy by aligning minimum inventory levels with fuel consumption across segments between bunkering ports. This study contributes to maritime management theory by synchronizing adaptive fuel inventory management with vessel deployment and speed optimization. There are practical implications for designing more resilient and cost-effective shipping strategies. Finally, this framework serves as a precursor tool for shipping liners to maintain service reliability while navigating the complexities of modern maritime logistics.